2020
DOI: 10.1177/2382120520943615
|View full text |Cite
|
Sign up to set email alerts
|

Preclerkship Point-of-Care Ultrasound: Image Acquisition and Clinical Transferability

Abstract: Introduction: The integration of point-of-care ultrasound (POCUS) in preclerkship medical education is currently popular and based on the notion that POCUS may improve diagnostic and procedural skills in medical students. However, empirical evidence demonstrating that POCUS can enhance clinical skills in preclerkship students has been lacking. We sought to evaluate anatomical sonographic knowledge and ultrasound generation capabilities associated with the implementation of a 3-h echocardiography training camp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 91 publications
0
7
0
Order By: Relevance
“…Fortunately, carefully designed content can optimize preparation by reducing cognitive load and positively influencing student engagement and motivation [22]. While manuals [23,24], PowerPoint presentations (PPs) [25,26] and video lectures [27,28] have been used to present various types of knowledge in flipped PS training, instructional theory suggests that PK is better learnt by the observation of a demonstration of the skill being performed [29]. Although demonstration videos (DVs) have been used as pre-skill conceptualisation in simulation-based flipped PS training in a handful of studies [7,8,[30][31][32][33], singly or in combination with other material, only 3 of these reported on objective measures of skills acquisition and presented conflicting results [7,8,31].…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, carefully designed content can optimize preparation by reducing cognitive load and positively influencing student engagement and motivation [22]. While manuals [23,24], PowerPoint presentations (PPs) [25,26] and video lectures [27,28] have been used to present various types of knowledge in flipped PS training, instructional theory suggests that PK is better learnt by the observation of a demonstration of the skill being performed [29]. Although demonstration videos (DVs) have been used as pre-skill conceptualisation in simulation-based flipped PS training in a handful of studies [7,8,[30][31][32][33], singly or in combination with other material, only 3 of these reported on objective measures of skills acquisition and presented conflicting results [7,8,31].…”
Section: Introductionmentioning
confidence: 99%
“…The University of Saskatchewan, since 2018, has published on a number of their innovative medical student POCUS education initiatives [ 26 , 27 ]. More recently the University of Ottawa published the results of on their pre-clerkship POCUS training [ 28 ]. With this increase incorporation of POCUS training in Canadian medical schools, we hypothesized that more recent cohorts of learners would enter residency with higher POCUS knowledge and skills.…”
Section: Discussionmentioning
confidence: 99%
“…They further demonstrated that electronic educational modules were as effective as traditional lectures for delivering such knowledge, although self-directed scan training on a high-fidelity simulator was not as effective as scan training by a sonographer [34]. Recently, several educational programs related to point-of-care cardiac ultrasound for undergraduate medical education were found to have positive outcomes, including eliciting improvements in confidence in obtaining proper images [35] and observed OSCE scores [36][37][38][39][40].…”
Section: Cardiac Ultrasoundmentioning
confidence: 99%